ANALISIS HARGA DAN KUALITAS PELAYANAN YANG MENDORONG MINAT PEMBELIAN APLIKASI ONLINE SHOP PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURRACHMAN SALEH SITUBONDO DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENIG - Priandani, Risqiyatun Jamilah Agustin; Hamdun, Edy Kusnadi; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Currently, the increase in internet users in Indonesia can create a better market for e-commerce industry users. One of them is online shopping. The purpose of this research is to analyze and test the influence of price and service quality that encourage interest in purchasing online shop applications among students at the Faculty of Economics and Business, Abdurrachman Saleh University, Situbondo, with Trust as an intervening variable. This research method is descriptive and quantitative. The technique used in this research is proportional stratified random sampling technique. With the populations of 709 and a sample of 88 respondents. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that price has a significant positive effect on trust, service quality has a significant positive effect on trust, price has a significant positive effect on purchase interest, service quality has a significant positive effect on purchase interest, trust has a positive effect but not significant effect on purchase interest, price has a positive but not significant effect on purchase interest through trust, service quality has a positive but not significant effect on purchase interest through trust.